Fabrication of 1000-Line/mm orthogonal grating for Micro-Deformation field mapping - Xinyun Xie; Qinghua Wang; Xiaojun Yan (Materials & Design)
High-frequency gratings are vital for microscale deformation field analysis but face fabrication challenges due to cost and complexity. In this study, we innovatively report a rapid fabrication technique of large-area 1000-line/mm (1 µm pitch) orthogonal grating using maskless lithography with a 405 nm UV light source, and apply it to characterize the microscale slip plastic deformation fields of a Nickel-Based Single Crystal superalloy (NBSC) specimen for the first time. Detailed fabrication parameters and quality assessments were outlined. Moreover, in-situ tensile experiments on NBSC specimen in the [001] tensile direction were performed, and the evolution of the microscale plastic deformation fields was obtained by the sampling moiré method. The results showed that the proposed technique enables the stable fabrication of 1000-line/mm grating with 300 nm feature linewidth, rates up to 20–30 min per 1 mm2. The 1000-line/mm grating enables nano-sensitive deformation resolution for plastic deformation displacement fields on the surface of the NBSC specimen. The proposed method provides a feasible deformation carrier fabrication technique to support microscale deformation measurement of various materials.